On Awangarda: Tradition and Modernity in Postwar Polish Music by Lisa Cooper Vest - Beszterda van Vliet, Marta (Res Facta Nova, 2022)
Awangarda: Tradition and Modernity in Postwar Polish Music (University of California Press, 2020) by Lisa Cooper Vest traces discourses of tradition, modernity, and progress in Polish new music composition between 1930 and 1965. Drawing on an extensive body of archival materials, Cooper Vest demonstrates ideas, interests, and stakes that were at play for different actors invested in the shifting musical milieu in mid-century Poland. This essay offers an overview of the book’s main arguments–including its new approach to the history of the Polish School–while highlighting the ways in which Cooper Vest’s work is compelling to Polish audiences. Rather than retreading the worn narrative of Polish post-war music culture as an extension of the broader East-West ideological conflict, Cooper Vest emphasizes the local Polish context. Mid-century musical discourse relied on a consensus that Poland had fallen behind on a fixed path of development. This idea of backwardness takes the form of two discursive gestures: lag and lack. Tracing the return of the nineteenth-century Romantic ideas about compositional genius, attributed first to Witold Lutosławski and later to a new group of young composers, Cooper Vest demonstrates that the Polish School phenomenon was a negotiated consensus, rather than a group that emerged organically. At the same time, the author documents the rise and fall of Bogusław Schaeffer and his individual vision for avant-garde composition. This unique contribution to the field of musicology also poses broader questions about mobilizing history and memory to consolidate a sense of national identity through music composition.